2016
DOI: 10.4103/1319-2442.185227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of efficacy and safety profile of rhubarb and α-keto analogs of essential amino acids supplementation in patients with diabetic nephropathy

Abstract: To determine the efficacy and safety profile of rhubarb and α-keto analogs of essential amino acids supplementation in patients of diabetic nephropathy (DN), we studied 96 patients of DN attending a tertiary care center of the North India. The patients were randomly divided into three equal interventional groups. Group I (control) that received conservative management along with placebo, Group II (rhubarb) that received conservative management along with rhubarb capsule (350 mg, thrice daily), and Group III [k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 1 publication
1
29
1
Order By: Relevance
“…The present study reveals body weight, blood glucose, HbA1c, serum insulin and GPX were significantly improved in diacerein treated diabetic rats. The findings of current study are consistent with earlier studies [17,[22][23][24]. A double-blind randomized placebo control trial was concluded that the diacerein has an effect on β-cell secretory physiology [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study reveals body weight, blood glucose, HbA1c, serum insulin and GPX were significantly improved in diacerein treated diabetic rats. The findings of current study are consistent with earlier studies [17,[22][23][24]. A double-blind randomized placebo control trial was concluded that the diacerein has an effect on β-cell secretory physiology [22].…”
Section: Discussionsupporting
confidence: 91%
“…The study evaluated the outcome of β-cell physiology by estimating and comparing the blood sugar and insulin in controls, diabetic controls and diacerein treated diabetic rats. The experimental and clinical trials have reported that diacereinis effective in treating diabetes mellitus [17], left ventricular dysfunction [18] and relieving the visceral pain [19]. A previous study reported its use in breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…A manual review of references cited in the studies yielded 2 additional citations, resulting in a total of 27 articles that were formally assessed for eligibility. Eleven of these studies were identified for the systematic review (Table 2) [2,8,12,[23][24][25][26][27][28][29][30]. Agreement between 2 researchers was high.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Ketoacid analogues of EAA (ketoanalogues; KA) can serve as substrates for protein synthesis without the production of toxic nitrogenous waste products [11]. Thus, supplementation of a protein-restricted diet with KA allows a reduced intake of nitrogen while avoiding the deleterious consequences of inadequate dietary protein intake, mainly on muscle metabolism [12]. In nondiabetic patients with CKD, supplementation of a low protein diet (LPD) or very-low-protein diet (VLPD) with KA has been shown to have additional advantages on uremic control, reduce CKD-related cardiovascular risk factors, attenuate the disease progression, and delay the requirement for maintenance dialysis therapy while being nutritionally safe [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Ketoanalogues of amino acids (KAs) are nitrogen-free analogs of essential amino acids. “Ketodiet” refers to a variety of KA and low-protein diets (LPDs; 0.6 g/kg per day) or very-low-protein diets (VLPDs; 0.3–0.4 g/kg per day), which allow a reduced intake of nitrogen while avoiding the deleterious consequences of inadequate dietary protein intake and malnourishment [6]. These diets have been proven effective in reducing renal death in selected, well-nourished, progressive CKD patients with proven diet adherence and low-comorbidity [7].…”
Section: Introductionmentioning
confidence: 99%